Parental social support, perceived competence and enjoyment in school physical activity - Bo Shen; Erin Centeio; Alex Garn; Jeffrey Martin; Noel Kulik; Cheryl Somers; Nate McCaughtry (Elsevier, 2018)
Background: Beginning in the elementary school years, there are differences among children on how they perceive their competence in physical activity (PA). Children's competence perceptions may influence their affective reactions to PA. A crucial question is how to motivate children who hold low competence perceptions to enhance their enjoyment and PA involvement. Because parents play critical roles in children's development and socialization, social support from parents can be an important factor to complement teachers' effort to enhance children's enjoyment and PA involvement. In this research we identified the associations among children's beliefs about parental social support, perceived competence, and enjoyment in school PA. Methods: Three hundred and twenty children (9-11 years old) participated in a two-wave study. At the first wave, children completed questionnaires measuring their beliefs about parental social support, perceived competence, and enjoyment in school PA; they reported their enjoyment again 8 months later at the second wave. Results: Both concurrent and longitudinal analyses revealed that beliefs about parental social support were important factors associated with children's enjoyment in school PA, especially among girls with low competence perceptions. Conclusion: Family socialization factors should be taken into consideration. The efficacy of individual and community-level strategies should be included and evaluated when designing effective intervention strategies that enhance children's PA in school. Keywords: Elementary children, Motivation, Social context, Social support